What is an independent art space? Using a text-mining approach to describe independent art spaces. Issue 5 (20th October 2022) - Vorobeva, Maria
ABSTRACT: The ability of independent art spaces to create new practices in the arts is recognised, alongside with their influence on the socio-economic development of places in which they appear. Yet, art spaces remain poorly understood, as present studies look only at individual examples of these places. In this paper, using text mining methods, 1537 descriptions of independent art spaces, located worldwide, are investigated to provide insights into what is an independent art space, by defining its common features. The study finds that independent art spaces are described as non-profit, artist-run places, striving to bring together local and international cultures and engage artists in cooperation. Besides, independent art spaces offer both public platforms and workplaces for artists, promoting creativity and experimental art. The identified features can contribute to the debate over the connection between art spaces and socio-economic development.